Functional inclusion bodies produced in the yeast Pichia pastoris. Issue 1 (December 2016) - Rueda, Fabián; Gasser, Brigitte; Sánchez-Chardi, Alejandro; Roldán, Mònica; Villegas, Sandra; Puxbaum, Verena; Ferrer-Miralles, Neus; Unzueta, Ugutz; Vázquez, Esther; Garcia-Fruitós, Elena; Mattanovich, Diethard; Villaverde, Antonio
Abstract Background Bacterial inclusion bodies (IBs) are non-toxic protein aggregates commonly produced in recombinant bacteria. They are formed by a mixture of highly stable amyloid-like fibrils and releasable protein species with a significant extent of secondary structure, and are often functional. As nano structured materials, they are gaining biomedical interest because of the combination of submicron size, mechanical stability and biological activity, together with their ability to interact with mammalian cell membranes for subsequent cell penetration in absence of toxicity. Since essentially any protein species can be obtained as IBs, these entities, as well as related protein clusters (e.g., aggresomes), are being explored in biocatalysis and in biomedicine as mechanically stable sources of functional protein. One of the major bottlenecks for uses of IBs in biological interfaces is their potential contamination with endotoxins from producing bacteria. Results To overcome this hurdle, we have explored here the controlled production of functional IBs in the yeastPichia pastoris (Komagataella spp.), an endotoxin-free host system for recombinant protein production, and determined the main physicochemical and biological traits of these materials. Quantitative and qualitative approaches clearly indicate the formation of IBs inside yeast, similar in morphology, size and biological activity to those produced inE. coli, that once purified, interact with mammalian cell membranes and penetrate cultured mammalian cells in absence of toxicity. Conclusions Structurally and functionally similar from those produced inE. coli, the controlled production of IBs inP. pastoris demonstrates that yeasts can be used as convenient platforms for the biological fabrication of self-organizing protein materials in absence of potential endotoxin contamination and with additional advantages regarding, among others, post-translational modifications often required for protein functionality.